Paclitaxel Ameliorates Lipopolysaccharide-Induced Kidney Injury by Binding Myeloid Differentiation Protein-2 to Block Toll-Like Receptor 4–Mediated Nuclear Factor-κB Activation and Cytokine Production - Zhang, Dongshan (The American Society for Pharmacology and Experimental Therapeutics, 2013)
Recent studies suggest that paclitaxel, an anticancer agent, may modulate the injury and inflammatory responses in normal tissues. However, the underlying mechanism is not fully understood. Here we have examined the effect of paclitaxel on lipopolysaccharide (LPS)–induced acute kidney injury (AKI) in mice and further studied the mechanism. At relatively low doses, paclitaxel protected against LPS-induced AKI and improved animal survival. The beneficial effects of paclitaxel were accompanied by the downregulation of tumor necrosis factor-α, interleukin-1, and interleukin-6 production. In cultured renal tubular HK-2 cells, paclitaxel decreased the DNA-binding activity of nuclear factor-κB (NF-κB) during LPS treatment, inhibited the degradation of the inhibitor of κB-α, and blocked the expression and activation of NF-κB p65. At the upstream level, paclitaxel reduced LPS-induced association of myeloid differentiation protein-2 (MD-2) with Toll-like receptor 4 (TLR4). In an in vitro assay, paclitaxel was shown to directly bind recombinant MD-2. The inhibitory effect of paclitaxel on NF-κB activation and cytokine expression disappeared in MD-2 knockdown cells, indicating that paclitaxel acts through MD-2. Collectively, these results suggest that paclitaxel may bind MD-2 to block MD-2/TLR4 association during LPS treatment, resulting in the suppression of NF-κB activation and inhibition of proinflammatory cytokine production.